Soft-bottom sipunculans in Izmir Bay (Aegean Sea, eastern Mediterranean) - Açik, Sermin (Zootaxa, 2009)
This paper deals with the sipunculan species distributed in Izmir Bay (Aegean Sea, eastern Mediterranean). Benthic samples were taken at 29 stations between 1998 and 2001 at depths ranging from 8 to 77 m. Six species and 200 individuals belonging to three families were found. Aspidosiphon (A.) mexicanus is newly recorded from Izmir Bay. The majority of specimens were found on a sandy-mud substratum (42%), followed by sand (35%), muddy-sand (19%) and sand (3%), respectively. Among the habitats, Posidonia oceanica and muddy-sand were represented by the highest numbers of species (4 species), followed by sandy-mud (3 species), and sand (2 species). The densities of the species at sampling stations were determined and compared seasonally, based on the data collected in 2001. Brief descriptions of the species and their distributional, reproductive and ecological characteristics are given.